Qaḍiyyat ʿIlm al-Dalālah ʿinda Toshihiko Izutsu - Kamal Musthofa (Lisanudhad: Jurnal Bahasa, Pembelajaran dan Sastra Arab, 2015)
The concept of language is no longer understood merely as a collection of sounds through which people express their intentions. Rather, language encompasses not only spoken expressions but also writing, signs, gestures, and other forms of communication that normally accompany verbal interaction. Among the scholars who devoted significant attention to the study of semantics is the Japanese linguist Toshihiko Izutsu, who is widely known for his theory of worldview (Weltanschauung) in semantic studies. Izutsu argued that an adequate and comprehensive conception of semantics had not yet been fully established. According to him, many existing interpretations of semantics fail to capture its true nature and therefore represent incomplete or distorted understandings of the discipline. This article aims to provide an in-depth examination of Toshihiko Izutsu's views on semantics by exploring the theoretical foundations of his semantic approach and its implications for understanding meaning within language.